Mitinha and Tamanduamyia, two new genera of Mythicomyiinae (Diptera, Mythicomyiidae) from northeast Brazil - Rafael, J.a.; Limeira-De-Oliveira, F. (Zootaxa, 2014)
Two new genera and two new species of Mythicomyiinae are described based on material collected in Parque Nacional Serra das Confusões, Piauí state, northeast Brazil, an arid region: Mitinha, gen. nov., type-species M. neri, sp. nov. and Tamanduamyia, gen. nov., type-species T. bandeira, sp. nov. An illustrated key is presented for world Mythicomyiinae genera.